Resilience of water supply systems – case study of Quinta do Lago - Caetano, João (2017)
On the South of Portugal, namely in Quinta do Lago – Algarve the water consumption pattern changes from winter to summer, mainly due to the seasonality of touristic occupation and irrigation of green areas. In Quinta do Lago many plots have boreholes to extract groundwater for irrigation, however in summer, when the irrigation demand has its peak, the groundwater table lowers and it is observed saline intrusion into the aquifer. The increased concentration of salts in groundwater also increases the water demand for irrigation as the soil lixiviation must be attended. This phenomenon forces the owners to irrigate the private green areas with fresh water from the water supply system. In the last years, the number of plots irrigated with fresh water has increased and the current trend may cause the failure of the water supply system. In the present study the hydraulic and operational performance of the water supply system of Quinta do Lago is assessed, considering the increase on water demand for the irrigation of the private green areas. The used methodology is based on the hydraulic modelling of the water supply system and evaluation of performance indicators using penalty functions. From the analysis it is pointed out that undertaking appropriate operational modes, the water supply system may be resilient to the increase in water demand and investment in new infrastructure to attend this phenomenon may not be required.